Nanoparticle-based antifungal therapies innovations mechanisms and future prospects - Qinglin Wu; Fulan Cen; Ying Xie; Xianjia Ning; Jinghua Wang; Zhenghao Lin; Jia Huang (PeerJ)
Fungal infections present an increasing global health challenge, with a substantial annual mortality rate of 1.6 million deaths each year in certain situations. The emergence of antifungal resistance has further complicated treatment strategies, underscoring the urgent need for novel therapeutic approaches. This review explores recent advances in nanoparticle-based therapies targeting fungal infections, emphasizing their unique potential to enhance drug solubility, bioavailability, and targeted delivery. Nanoparticles offer the ability to penetrate biological barriers, improve drug stability, and act as direct antifungal agents by disrupting fungal cell walls and generating reactive oxygen species. Despite their promising applications, challenges such as potential toxicity, scalability of production, and the need for controlled drug release remain. Future research should focus on optimizing nanoparticle properties, evaluating long-term safety profiles, developing environmentally sustainable synthesis methods, and exploring synergistic approaches with existing antifungal drugs. Nanotechnology offers a transformative opportunity in the management of fungal diseases, paving the way for more effective and targeted treatments.